Feeling Political - Frevert, Ute. author. aut Link
XIX, 390 p. 26 illus.
Keywords: Historicizing both emotions and politics, this open access book argues that the historical work of emotion is most clearly understood in terms of the dynamics of institutionalization. This is shown in twelve case studies that focus on decisive moments in European and US history from 1800 until today. Each case study clarifies how emotions were central to people’s political engagement and its effects. The sources range from parliamentary buildings and social movements, to images and speeches of presidents, from fascist cemeteries to the International Criminal Court. Both the timeframe and the geographical focus have been chosen to highlight the increasingly participatory character of nineteenth- and twentieth-century politics, which is inconceivable without the work of emotions. .